Functional problems in patients with colostomy caused by colorectal cancer in HRQOL research - Wiraszka, Grażyna R. (Nursing Problems / Problemy Pielęgniarstwa, 2007)
Background. Colorectal cancer belongs to a group of the most frequently occurring malignant cancer and considerable numbers of cases surgically treated end is stomy. Aim. The aim of the research was assessment of problems of biopsychosocial functioning in patients with colorectal cancer whose radical - surgical treatment ended in colostomy . Material and methods. The research was carried out from 2002 to 2003 on 164 patients at Świętokrzyskie Oncology Centre in Kielce. The control group consisted of 82 persons. The FACT-C questionnaire was used to collect the data. Results and conclusions. Statistical analysis of the research material showed that colostomy created as a result of surgical treatment for colorectal cancer caused considerable limitations of patients functioning in terms of physical condition, especially emotional and social life.